Reimagining Society in 18th Century French Literature - Ross Kjærgård, Jonas, author.
1 online resource (238 pages)
Keywords: The French revolutionary shift from monarchical to popular sovereignty came clothed in a new political language, a significant part of which was a strange coupling of happiness and rights. In Old Regime ideology, Frenchmen were considered subjects who had no need of understanding why what was prescribed to them would be in the interest of their happiness. The 1789 Declaration of the Rights of Man and of the Citizen equipped the French with a list of inalienable rights and if society would respect those rights, the happiness of all would materialize. This volume explores the authors of fictional literature who contributed alongside pamphleteers, politicians, and philosophers to the establishment of this new political arena, filled with sometimes vague, yet insisting notions of happiness and rights. The shift from monarchical to popular sovereignty and the corollary transition from subjects to citizens culminated in the summer of 1789 but it was preceded by an immense piece of imaginative work.